2012
DOI: 10.1016/j.vetpar.2011.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Widespread exposure to Sarcoptes scabiei in wild European rabbits (Oryctolagus cuniculus) in Spain

Abstract: a b s t r a c t Sarcoptic mange was recently described in the wild European rabbit (Oryctolagus cuniculus) in north-eastern Mediterranean Spain, the first such infection reported in this species anywhere in the world. This finding has created concern in conservationists and game managers given that an outbreak of mange after a translocation would have catastrophic consequences for naïve rabbit populations in other parts of Spain. A retrospective serosurvey using an 'in house' ELISA test based on the use of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…× Pig IgG4086[145] hominis Ssλ20ΔB3pigHRP-? × Pig IgG6283[145] hominis Ssλ20ΔB3rabbitHRP-Protein A100[108] hominis Ssλ20ΔB3rabbitHRP-Protein A9597[146] hominis Ssλ20ΔB3wolfHRP-Protein A7588[147] hominis rSsGST01humanAP-? × Hu IgV[148] hominis rSj26GSThumanAP-?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…× Pig IgG4086[145] hominis Ssλ20ΔB3pigHRP-? × Pig IgG6283[145] hominis Ssλ20ΔB3rabbitHRP-Protein A100[108] hominis Ssλ20ΔB3rabbitHRP-Protein A9597[146] hominis Ssλ20ΔB3wolfHRP-Protein A7588[147] hominis rSsGST01humanAP-? × Hu IgV[148] hominis rSj26GSThumanAP-?…”
Section: Introductionmentioning
confidence: 99%
“…The wild European rabbit ( Oryctolagus cuniculus ) occurs in north-eastern Mediterranean Spain and serves as prey for many predators as well as game for hunters [108]. Sarcoptes scabiei parasitizes some populations of these rabbits and there is concern that the disease can significantly affect the rabbit population and that it might be transmitted to other wildlife.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specificity was lower because about 10% of rabbits without mange lesions detected were seropositive in the ELISA. These animals could be at the beginning of the infestation before lesions become visible, or some could be already recovering from an infestation (Millán et al, 2012). In fact, in experimentally infested wild rabbits (n = 2), antibodies were detected up to five weeks before lesions were seen (Millán et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoptic mange was shown to be widespread in wild rabbits of the Iberian Peninsula, a retrospective serological survey demonstrated antibodies in 60% of the 53 areas studied showing that the disease has been present from at least the 1990s (Millán et al, 2012). Moreover, cases of sarcoptic mange were described in the wild European rabbit (Oryctolagus cuniculus) in north-eastern Mediterranean Spain (Millán, 2010;Navarro-Gonzalez et al, 2010), the first such infestation reported in this species anywhere in the world.…”
Section: Introductionmentioning
confidence: 96%